2006
DOI: 10.1021/bm060199t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Multiblock Copolymers Based on Spider Dragline Silk Proteins

Abstract: Spider dragline silk with its superlative tensile properties provides an ideal system to study the relationship between morphology and mechanical properties of a structural protein. Accordingly, we synthesized two hybrid multiblock copolymers by condensing poly(alanine) [(Ala)(5)] blocks of the structural proteins (spidroin MaSp1 and MaSp2) of spider dragline silk with different oligomers of isoprene (2200 and 5000 Da) having reactive end groups. The synthetic multiblock polymer displayed similar secondary str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 32 publications
0
58
0
1
Order By: Relevance
“…This peak can be assigned to the intermolecular spacing between oligopeptides within a b-sheet tape. Notably, however, it is significantly smaller than the typical value of B4.8 Å observed in proteins, due to strong hydrogen bonding in the hydrophobic matrix 20,30,45,46 . Moreover, M2-M5 exhibited an additional reflection at a spacing of 5.3-5.4 Å, corresponding to the intersheet distance between stacked b-sheets observed in poly(L-alanine) 45 , spider silk (5.30 Å) 47 or related materials 20,30,46 (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…This peak can be assigned to the intermolecular spacing between oligopeptides within a b-sheet tape. Notably, however, it is significantly smaller than the typical value of B4.8 Å observed in proteins, due to strong hydrogen bonding in the hydrophobic matrix 20,30,45,46 . Moreover, M2-M5 exhibited an additional reflection at a spacing of 5.3-5.4 Å, corresponding to the intersheet distance between stacked b-sheets observed in poly(L-alanine) 45 , spider silk (5.30 Å) 47 or related materials 20,30,46 (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Poly(alanylglycine) and poly(alanine) present in spider silk proteins are responsible for crystallinity and hence stiffness of fibers made thereof. A number of silk-inspired polymers containing blocks of -sheet-forming peptides [GA] n or (A) nn and flexible linkers like PEG [poly(ethylene glycol)] have been reported [94][95][96][97][98]. The Sogah group has published the most comprehensive studies of silk-inspired polymers [99,100].…”
Section: Silk Inspired Synthetic Polymersmentioning
confidence: 99%
“…Instead, the central β-sheet domains stacked together in an orderly fashion to form well-defined fibrils (Smeenk et al, 2005). Zhou et al (2006) reported a series of silk-like multiblock peptide-polymer hybrids containing A5 blocks and polyisoprene oligomers (PI). The PI oligomer improved the solubility of the hybrid polymer, just as glycine-rich domains do in natural silk proteins.…”
Section: Polymer-peptide Hybrids Inspired By Silk Proteinsmentioning
confidence: 99%